2021
DOI: 10.1186/s12909-021-02664-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the practice, confidence and educational needs of hospital pharmacists in reviewing antimicrobial prescribing: a cross-sectional, nationwide survey

Abstract: Background Antimicrobial stewardship (AMS) programs are usually limited in resources and scope. Therefore, wider engagement of hospital pharmacists in reviewing antimicrobial orders is necessary to ensure appropriate prescribing. We assessed hospital pharmacists’ self-reported practice and confidence in reviewing antimicrobial prescribing, and their knowledge in making AMS interventions. Methods We conducted an Australia-wide, cross-sectional surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 24 publications
0
13
2
Order By: Relevance
“…Consistent with this, a recent national survey of Australian hospital pharmacists determined that those with two years or less of registration lacked the confidence to identify AMS interventions compared to more experienced hospital pharmacists. 12 However, in our study, pharmacists with more than two years of experience also reported benefits from coaching.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Consistent with this, a recent national survey of Australian hospital pharmacists determined that those with two years or less of registration lacked the confidence to identify AMS interventions compared to more experienced hospital pharmacists. 12 However, in our study, pharmacists with more than two years of experience also reported benefits from coaching.…”
Section: Discussionmentioning
confidence: 48%
“… 9 , 10 In the Australian pharmacist survey mentioned above, interactive modes of education delivery such as a rotation in ID/AMS under supervision, one-on-one mentoring/coaching, and interactive small groups were perceived by a higher proportion of respondents to be useful or very useful than more didactic options such as lectures and e-learning modules. 12 Similarly, in the Malaysian study, a higher proportion of survey respondents preferred to learn about AMS via hands-on, experiential, or mentoring activities. 13 This pilot study aimed to describe for the first time the use of an interactive educational coaching approach to AMS targeted at ward pharmacists.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, less than half were confident in changing the antimicrobial spectrum in particular and overall junior pharmacists lack confidence in identifying AMS intervention compared with more experienced pharmacists. 7 This study results highlighted the necessity to address gaps in undergraduate curricula in AMS and AMR field. Another study, in Qatar, indicated there were many gaps between AMS education and clinical practice, and recommended making AMS and AMR compulsory elements on undergraduate curricula.…”
Section: Introductionmentioning
confidence: 77%
“…11 Another study assessed pharmacists AMS knowledge also clearly highlighted the gap in undergraduate curricula regarding this subject. 7 Thus, it may be suggested that pharmacy colleges curriculum content of infectious diseases such as AMR and AMS be assessed by qualified and experienced pharmacists in the field, from both clinical practice and academia. Also, the 2017 KSA MoH recommendation to pharmacy colleges should be monitored, evaluated, improved and studied.…”
mentioning
confidence: 99%